Faktor-Faktor Yang Mempengaruhi Malnutrisi - Muhammad Ihsan Fariqy; Graharti, Risti (CV. Jasa Sukses Abadi, 2024)
Malnutrition in children is a serious issue that can impact both health and optimal growth. This condition arises from a nutritional imbalance, involving an excess or deficiency of calories, protein, and other essential nutrients. Risk factors include socio-economic status, maternal lack of awareness, Low Birth Weight (LBW), family food intake, infections, maternal education, breastfeeding practices, and environmental sanitation. Clinical manifestations of malnutrition encompass stunted growth, dry skin and hair, fatigue, decreased appetite, and motor development disorders. Effective preventive efforts require a holistic approach, including heightened public awareness of nutrition, changes in social and economic policies, and improvements in environmental sanitation. By understanding and addressing these factors, it is hoped that the prevalence of malnutrition can be reduced, thereby enhancing the overall quality of life for children worldwide.